The Role of the Intelkam Political Unit in Promoting Preparations for the 2024 Election in the Jurisdiction of the Malang City Police - Patriatama, Muhammad Lembayung Putra (Advances in Police Science Research Journal, 2024)
This research was motivated by disturbances in security and public order (kamtibmas) during the 2019 elections in the jurisdiction of Malang City. The Intelligence and Security Unit (Intelkam) of the Malang City Police, especially the Political Unit, plays an important role in mobilizing to ensure the smooth running of the 2024 elections and control disturbances to social security and order. A qualitative approach was used in this research by referring to role theory, POAC management, 4M management, as well as the concepts of security intelligence, intelligence gathering and elections from previous research. The results of data analysis show that the role and implementation of fundraising by the Political Unit of the Malang City Police Intelligence and Security Unit in the 2024 Election can be understood through the POAC role and management theory. Next, the factors that influence the implementation of the fundraising are analyzed using the 4M management theory. The conclusion of this research is that the role and implementation of the Political Unit of the Malang City Police Intelligence and Security Unit is not fully in accordance with the provisions stipulated in PERKABIK. There are also factors that influence the implementation of the 2024 election campaign by the Political Unit of the Malang City Police Intelligence and Security Unit.